Avaliação da infecção de megacariócitos e plaquetas pelo VHC e sua influência na fisiopatologia da hepatite C - Watanabe, Caroline Mitiká [UNESP] (2016)
Hepatitis C affects about 130-150 million people worldwide. It´s caused by Hepacivirus and the diagnosis are by extrahepatic symptoms such as chronic fatigue, endocrine, dermatologic and hematologic changes. However, the pathogenesis of extrahepatic manifestations is little known and requires further studies on the relationship of these disorders and the hepatitis C vírus (HCV), therefore infection in vitro model can improve this kind of knowledge. HCV is a family of Flaviviridae, its entry into susceptible cells, such as hepatocytes, can occur by direct infection mediated primarily by CD81 receptors and Claudin-1 (CLDN1), triggering a process serie for internalization and viral replication ocurr. Other road is by cell-to-cell mediated CLDN1 and occludin (OCLN), not being necessary the presence of CD81. Studies describe the interaction between platelets and HCV, however, does not clearly denotes how this process happens, due to this, studies can contribute to the elucidation of this process relevance. The aim of this study is the evaluation of the infection of megakaryocytes and platelets HCV and the influence in pathophysiology of hepatitis C. Megakaryocytes samples, from bone marrow donors, and samples of peripheral platelets, both obtained from healthy donos are infected in vitro with HCV positive plasma. Infected samples were evaluated by flow cytometry and confocal microscopy. The parameters analyzed were the presence or absence of viral and expression of CLDN1 and CD81 receptors. The results of both techniques are complementary. It was founded the presence of HCV both in surface and in cytoplasm of platelets by flow cytometry and confocal microscopy, fact not previously reported. The receptor analysis showed the presence of CLDN1, one of the proteins involved in the viral transmission cell-cell, so the interaction can occur in this via. CD81 was absent, as reported in literature. Megakaryocytes also had HCV on the surface and inside the cells. They express CD81 and CLDN-1, so then are susceptible to viruses via direct infection. Reports in the literature suggest that this cell can support viral replication, and can be considered as extrahepatic replication reservoir. Studies conducted independently demonstrated that HCV infection in platelets and megakaryocytes is related to peripheral thrombocytopenia. In addition, secondary factors such as hepatic damage, affect the levels and production of thrombopoietin, the main factor in maintaining trombopoese process. The study found virus at surface and in the cytoplasm of platelet infected in vitro, indicating that platelet can interacting with HCV an can be a vehicles to the infection or reservoir of HCV. In addition, megakaryocytes are infected in vitro with the virus, which can produce platelets infected ou be a reservoir of HCV, since these are the platelet precursors. This findings demonstrate an infection model efficient and can contribute to the understanding of thrombocytopenia and extrahepatic manifestations, commonly observed in patients with chronic hepatitis C Keywords: In vitro infection; megakaryocytes; platelets; Hepatitis C virus.